PENGARUH KEMAMPUAN MENGGAMBAR MOTIF TERHADAP HASIL BELAJAR KRIYA BATIK SISWA KELAS XI DI SMKN 8 PADANG - Vanesha Miswar (Institut Seni Indonesia Padangpanjang, 2022)
This research is a quantitative research. The data were analyzed using descriptive statistical analysis. This research aimed to determine the effect of ability to drawing motifs of class XI at SMKN 8 Padang and the factors that influence the ability to drawing motifs. The population in this research were students of class XI majoring in Textile Crafts department at SMKN 8. Meanwhile, the sample was selected based on